A deafness-associated tRNAAsp mutation alters the m1G37 modification, aminoacylation and stability of tRNAAsp and mitochondrial function. Issue 22 (17th August 2016) - Wang, Meng; Peng, Yanyan; Zheng, Jing; Zheng, Binjiao; Jin, Xiaofen; Liu, Hao; Wang, Yong; Tang, Xiaowen; Huang, Taosheng; Jiang, Pingping; Guan, Min-Xin
Abstract: In this report, we investigated the pathogenic mechanism underlying the deafness-associated mitochondrial(mt) tRNA Asp 7551A > G mutation. The m.7551A > G mutation is localized at a highly conserved nucleotide(A37), adjacent (3΄) to the anticodon, which is important for the fidelity of codon recognition and stabilization in functional tRNAs. It was anticipated that the m.7551A > G mutation altered the structure and function of mt-tRNA Asp . The primer extension assay demonstrated that the m.7551A > G mutation created the m 1 G37 modification of mt-tRNA Asp . Using cybrid cell lines generated by transferring mitochondria from lymphoblastoid cell lines derived from a Chinese family into mitochondrial DNA(mtDNA)-less ( ρ o ) cells, we demonstrated the significant decreases in the efficiency of aminoacylation and steady-state level of mt-tRNA Asp in mutant cybrids, compared with control cybrids. A failure in metabolism of mt-tRNA Asp caused the variable reductions in mtDNA-encoded polypeptides in mutant cybrids. Impaired mitochondrial translation led to the respiratory phenotype in mutant cybrids. The respiratory deficiency lowed mitochondrial adenosine triphosphate production and increased the production of oxidative reactive species in mutant cybrids. Our data demonstrated that mitochondrial dysfunctions caused by the m.7551A > G mutation are associated with deafness. Our findings may provide new insights into the pathophysiology of maternally transmitted deafness that was manifested by altered nucleotide modification of mitochondrial tRNA.